The Influence of Organizational Culture and Personality on Employee Performance with Organizational Commitment as an Intervening Variable at Company: Pengaruh Budaya Organisasi dan Kepribadian terhadap Employee Performance dengan Organizational Commitment sebagai Variabel Intervening pada Perusahaan - Irmawati, Denis; Andriani, Dewi (Indonesian Journal of Law and Economics Review, 2023)
This study aims to determine the influence of organizational culture and personality on employee performance with Organizational Commitment as an intervening variable at Pt. Plywood Kayu Lestari Mojokerto City.This research uses quantitative research with hypothesis testing. The sample used in this study were 110 employees at Pt. Sustainable Wood Plywood. The analytical tool used in this research is path analysis technique with the help of statistical software. The primary data in this study were obtained from a questionnaire whose measurement was using a Likert scale which was tested for validity and reliability. The results of this study prove that (1) organizational culture is positively and significantly related to Organizational Commitment (2) personality is positively and significantly related to Organizational Commitment (3) organizational culture is positively and significantly related to employee performance (4) personality has a positive and significant effect on employees performance (5) Organizational Commitment has a positive and significant effect on employee performance (6) organizational culture is positively and significantly related to employee performance and Organizational Commitment (7) personality is positively and significantly related to employee performance and Organizational Commitment.